WAYS TO INCREASE THE WORK EFFICIENCY OF WORKING BODIES MACHINED WITH A SHAPED CUTTER (Conference Zone, 2022)
Using pneumatic transport, the raw material of cotton, which enters the working chamber of the baler in bulk, is crushed by mechanical processing with the help of a shaped cutter on the blade drum shaft mounted on the device in order to reduce seed damage.